Evaluasi Medical Response Preparedness Pada Unit Gawat Darurat (Studi Kasus di IGD Rumah Sakit Umum Pusat Dr. Sardjito Yogyakarta) - Indah Puspitasari; Nur Aini Masruroh (Forum Teknik, 2015)
In the last decade, there were 2 disasters that killed many people in Yogyakarta, such as earthquake in 2006 and Merapi eruption in 2010. Therefore, as one of reference hospitals,RSUP Dr. Sardjito must have good medical response preparedness to handle victims that were evacuated to RSUP Dr. Sardjito, therefore evaluation of medical response preparedness that has been applied in RSUP Dr. Sardjito is needed, in purpose deciding resources allocation.Simulation is used to evaluate medical response preparedness. Model is built based on real system when Merapi eruption is happened and on extreme points of arrival rate of victims to RSUP Dr. Sardjito, that is on 5 and 7 November 2010. Then the model is simulated and evaluated by using average waiting time for victims to be handled as indicator. The evaluation result will decide resources allocation that is needed. simulation of model 5 November results average waiting time for patient with severity 1, 2, 3, and 4 is 2991,26; 72,19; 0; 0 minutes. While model 7 November results waiting time for patient with severity 2, 3, and 4 is 0,22; 0; 0 minutes. From the results, sensitivity analysis is used to decide resources allocation needs.Keywords: medical responses, emergency department, simulation, disaster, system improvement